Analisis Keterampilan Pengambilan Keputusan pada Pemecahan Masalah Fisika Peserta Didik Kelas X SMA N 1 Mranggen - Utami, Alifa Citra; Khoiri, Nur; Saefan, Joko; Ristanto, Sigit (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
This research aims to analyze the level of students' skills in the case of renewable energy physical material problems in solar power plants. This research method is quantitative. The research subjects consisted of 36 class X SMA N 1 Mranggen students. Data collection techniques include tests, observation, and documentation. The research instruments used were test and observation instruments. Based on the results of the research that has been conducted, it shows that the decision-making skills of students in the high category are 10 (27.8%). A total of 21 students (58.3%) still have medium ability, and 5 students (13.9%) have low ability.